Nepali Paintings and Poetry: Reviews and Reflections (SIRJANĀ – A Journal Of Arts and Art Education, 2017)
This topic has been lodging with me for over three decades. During this period of time it has continued to pose me new challenges and new excitements of openings. I have written some essays on this topic. I am basically a literary person who writes poems, plays, essays, art criticism and theoretical aspects of both genres of art - paintings and poetry. As a teacher I have taught these subjects all my life. But saying final words does not worry me because despite efforts by art critics, historians and literary writers to draw common grounds for both literature and art, it has yielded mixed results everywhere. One thing is always certain - the comparisons remain incomplete in terms of drawing either a fine line between arts and poetry, and showing the unique merger between the two forms of art. Some subjects remain exciting in their incomplete states. That happens as a matter of exigency, which means the incompletion of comparison is necessitated by the nature of the subject itself. As this is a very big subject, attempt is made to narrow it down to the poetic experience. Affinity of the genre of literature, especially of poetry, to art constitutes the subject matter for this article.